Sustaining and Accelerating Pro-Poor Growth in Africa - Carey, Kevin (International Monetary Fund, 2006)
Growth in sub-Saharan Africa has recently shown signs of improvement, but is still short of levels needed to attain the Millennium Development Goals. Economists have placed increasing emphasis on understanding the policies that promote sustained jumps in medium-term growth, and the paper applies this approach to African countries. The evidence presented finds an important growth-supporting role for particular kinds of institutions and policies, but also highlights aspects of growth that are still not well understood. The paper includes policy guidance for ensuring that the poor benefit from growth.